2022
DOI: 10.1155/2022/7676582
|View full text |Cite|
|
Sign up to set email alerts
|

Alpha Protein Kinase 2 Promotes Esophageal Cancer via Integrin Alpha 11

Abstract: Background. As a common disease around the world, esophageal cancer (EC) primarily includes two subclasses: esophageal adenocarcinoma and esophageal squamous cell carcinoma. Mortality has been rising over the years; hence, exploring the mechanism of EC development has become critical. Among the alpha protein kinases, alpha protein kinase 2 (ALPK2) presumably has a connection with EC, but it has never been revealed before. Methods. In this study, IHC analysis was used for ALPK2 expression quantification in ES t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…Elevated ALPK2 levels signifcantly diminished overall survival in OCLM patients, aligning with prior studies associating increased ALPK2 expression with aggressive tumor behavior in other cancer types [18]. Tis suggests that ALPK2 may not only serve as a prognostic marker but could also potentially act as a mechanistic driver of tumor progression [10][11][12]. Te signifcance of age as a factor afecting overall survival emphasizes the importance of early detection and targeted interventions.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Elevated ALPK2 levels signifcantly diminished overall survival in OCLM patients, aligning with prior studies associating increased ALPK2 expression with aggressive tumor behavior in other cancer types [18]. Tis suggests that ALPK2 may not only serve as a prognostic marker but could also potentially act as a mechanistic driver of tumor progression [10][11][12]. Te signifcance of age as a factor afecting overall survival emphasizes the importance of early detection and targeted interventions.…”
Section: Discussionsupporting
confidence: 80%
“…Te signalling mechanisms through which ALPK2 operates in this context are yet to be fully elucidated, but its involvement suggests a potential regulatory role in pathways governing cell proliferation and metastasis [9]. Similarly, ALPK2 has been implicated in promoting aggressiveness through multiple signalling pathways in bladder cancer, esophageal cancer, and nonsmall lung cancer [10][11][12]. Te precise molecular mechanisms by which ALPK2 contributes to tumor progression involve intricate crosstalk with signalling cascades associated with increased cell motility, invasion, and resistance to apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Ainiwaer et al. found that ALPK2, as a downstream target gene, promotes ESCC tumor cell migration in vascular endothelial cells by regulating ITGα11 ( 62 ) ( Figure 1 ).…”
Section: Mechanism Of Esophageal Cancer Metastasismentioning
confidence: 99%
“…ITGA11 influences prognosis by promoting cancer-associated fibroblast (CAF) migration. [6][7][8][9][10][11][12][13][14] Furthermore, ITGA11 is critical in myofibroblast differentiation, matrix reorganization, and collagen deposition. 15,16 ITGA11 is overexpressed in CAFs, contributing to tumor matrix construction and affecting the overall survival of patients with head and neck squamous cell carcinoma.…”
Section: Introductionmentioning
confidence: 99%